A exclusão do (não)sujeito imigrante a partir da ideia de exceção: uma análise das constituições de 1934 a 1988 - Dode Junior, Hermes Correa (2018)
The dissertation aims at first to establish a concept of State of Exception according to the Agambem logic. Following these theoretical contributions, we try to explain why the State of Exception logic is strictly connected to the Democratic State of Law becoming so the State of Exception no more an exception but a rule, term we use as Permanent State of Exception, sense we look for unhiding the true intentions of Nation-state. Soon we bring into discussion the immigrant who will in this security conjecture be nominated as non-subjects because the power structures are shaped for their exclusion. We do the critics about the sovereignty theories that legitimate the Permanent State of Exception with the intention to restrict human mobility segregating the immigrant by policies of maintenance of the neoliberal state, like hidden universalization and the big problems in the world. We are distinct subjects, and the idea of homogenization – brought by the concept of universalization – reproduces a silent violence in the other, putting the immigrant as an enemy of the State with the security speech. In the final chapter, we do a historical survey about Brazilian constitutions of 1934 and 1964 and also their migratory legislation about migration, seen that that all those constitutions have an ethos of exception. At the end, we discuss about the constitution of 1988 and its exclusive character with respect to citizenship and nationality pointing the advances and regressions in the new Brazilian law of migration (law n°13.445/2017). Therefore, we conclude that the assumption that the right of migration should not be treated as an economical ou security policy but as a human right to migrate.